Technical Note: Display window setting: An important factor for detecting subtle but clinically relevant artifacts in daily CT quality control. Issue 12 (10th November 2016) - Long, Zaiyang; Bruesewitz, Michael R.; Sheedy, Emily N.; Powell, Michele A.; Kramer, Jacqualynn C.; Supalla, Randall R.; Colvin, Chance M.; Bechel, Jessica R.; Favazza, Christopher P.; Kofler, James M.; Leng, Shuai; McCollough, Cynthia H.; et al.
Abstract : Purpose: This study aimed to investigate the influence of display window setting on technologist performance detecting subtle but clinically relevant artifacts in daily computed tomography (CT) quality control (dQC) images. Methods: Fifty three sets of dQC images were retrospectively selected, including 30 sets without artifacts, and 23 with subtle but clinically relevant artifacts. They were randomized and shown to six CT technologists (two new and four experienced). Each technologist reviewed all images in each of two sessions, one with a display window width (WW) of 100 HU, which is currently recommended by the American College of Radiology, and the other with a narrow WW of 40 HU, both at a window level of 0 HU. For each case, technologists rated the presence of image artifacts based on a five point scale. The area under the receiver operating characteristic curve (AUC) was used to evaluate the artifact detection performance. Results: At a WW of 100 HU, the AUC (95% confidence interval) was 0.658 (0.576, 0.740), 0.532 (0.429, 0.635), and 0.616 (0.543, 0.619) for the experienced, new, and all technologists, respectively. At a WW of 40 HU, the AUC was 0.768 (0.687, 0.850), 0.546 (0.433, 0.658), and 0.694 (0.619, 0.769), respectively. The performance significantly improved at WW of 40 HU for experienced technologists ( p = 0.009) and for all technologists ( p = 0.040). Conclusions: Use of a narrow display WW significantly improved technologists' performance in dQC for detecting subtle but clinically relevant artifacts as compared to that using a 100 HU display WW.